Diagnosis of giant cell arteritis by temporal artery biopsy is associated with biopsy length - Ruediger, Carlee; Ninan, Jem; Dyer, Kathryn; Lyne, Suellen; Tieu, Joanna; Black, Rachel J.; Dodd, Thomas; Lester, Susan; Hill, Catherine L. (Frontiers in Medicine, 2022)
AIMS: Temporal artery biopsy is the primary method for establishing a diagnosis of GCA. The optimal temporal artery biopsy (TAB) length for accurate histological GCA diagnosis has been suggested as 15mm post-fixation (15–20mm pre fixation). The aim of this study was to determine the relationship between a histological GCA diagnosis and optimal TAB length in the South Australian (SA) population. METHODS: Pre-fixation TAB length (mm) was reported in 825/859 of all samples submitted to SA Pathology between 2014-2020 from people aged 50 and over. When more than one biopsy was taken, the longest length was recorded. Analyses of both TAB length and TAB positive proportions were performed by multivariable linear and logistic regression analysis, including covariates sex, age and calendar year. RESULTS: The median age of participants was 72 (IQR 65, 79) years, 549 (66%) were female. The TAB positive proportion was 172/825 (21%) with a median biopsy length of 14mm (IQR 9, 18). Biopsy length (mm) was shorter in females (p = 0.001), increased with age (p = 0.006), and a small positive linear trend with calendar year was observed (p = 0.015). The TAB positive proportion was related to older age (slope/decade: 6%, 95% CI 3.6, 8.3, p < 0.001) and to TAB length (slope/mm 0.6%, 95% CI 0.2, 0.9), p = 0.002), but not sex or calendar year. Comparison of models with TAB length cut-points at 5, 10, 15, 20 mm in terms of diagnostic yield, receiver operating characteristics and Akaike Information Criteria confirmed >= 15mm as an appropriate, recommended TAB length. However only 383 (46%) of the biopsies in our study met this criteria. The diagnostic yield at this cut-point was estimated as 25% which equates to an expected additional 30 histologically diagnosed GCA patients. Conclusion: This study confirms that TAB biopsy length is a determinant of a histological GCA diagnosis, and confirms that a TAB length >= 15mm is optimal. Approximately half the biopsies in this study were shorter than this optimal length, which has likely led to under-diagnosis of biopsy-proven GCA in SA. Further work is needed to ensure appropriate TAB biopsy length.